From Magneto-Dielectric Biocomposite Films to Microstrip Antenna Devices - Casagrande-Denardin, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Magneto-dielectric composites are interesting advanced materials principally due to their potential applications in electronic fields, such as in microstrip antennas substrates. In this work, we developed superparamagnetic polymer-based films using the biopolymeric matrices chitosan (Ch), cellulose (BC) and collagen (Col). For this proposal, we synthesized superparamagnetic iron oxide nanoparticles (SPIONs) functionalized with polyethyleneimine with a cheap method using sonochemistry. Further, the SPIONs were dispersed into polymer matrices and the composites were evaluated regarding morphology, thermal, dielectric and magnetic properties and their application as microstrip antennas substrates. Microscopically, all tested films presented a uniform dispersion profile, principally due to polyethyleneimine coating. Under an operating frequency (fo) of 4.45 GHz, Ch, BC and Col-based SPION substrates showed moderate dielectric constant (ε′) values in the range of 5.2–8.3, 6.7–8.4 and 5.9–9.1, respectively. Furthermore, the prepared films showed no hysteresis loop, thereby providing evidence of superparamagnetism. The microstrip antennas showed considerable bandwidths (3.37–6.34%) and a return loss lower than −10 dB. Besides, the fo were modulated according to the addition of SPIONs, varying in the range of 4.69–5.55, 4.63–5.18 and 4.93–5.44 GHz, for Ch, BC and Col-based substrates, respectively. Moreover, considering best modulation of ε′ and fo, the Ch-based SPION film showed the most suitable profile as a microstrip antenna substrate. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.